Assessment of Risk-Taking Behaviour of Young Motorcyclists at Un-Signalised Intersections – A Partial Least Square Structural Equation Modelling Approach - Abdul Basit, Hafiz; Khattak, Afaq; Abbas, Qalab; Arsalan Abbas, Sardar; Hussain, Arshad (Promet - Traffic&Transportation, 2022)
At un-signalised at-grade intersections or roundabouts, motorcyclists have to make a quick decision to manoeuvre and avoid crash. Many studies show that risk-taking behaviour is the major cause of accidents in young motorcyclists. In this study, we analysed various factors that are involved in the risk-taking behaviour of young motorcyclists at un-signalised intersections. Online questionnaires were distributed among university and college students in Islamabad and Rawalpindi. The data of 490 respondents were collected to test the research model. Partial least square structural equation modelling approach was used to evaluate the measurement model, structural model and importance-performance map analysis. In this study, we assumed that risk-taking behaviour of young motorcyclists at un-signalised intersections could be influenced by several factors, i.e., demographic, past crash involvement, and peer influence. The results revealed that past crash involvement, confidence level, and peer influence were the significant factors that affect the risk-taking behaviour. Peer influence has the highest effect on the risk-taking behaviour. The person whose friends encourage them to take risk and accept challenges is more likely to exhibit the risk-taking behaviour. Those people who are more confident while riding a motorcycle are more likely to take risks.